Update of Neuroanaesthesia in Bangladesh (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
In the last 20 years , new drugs and new methods of cerebral monitoring have been introduced, that have affected our choice & conduct of anaesthesia. Which affects significantly the outcome of neurosurgery. To consider the outcome from neurosurgical anaesthesia, both drugs & monitors have to be considered. This is a retrospective study of 2000 patients those who attended in BSMMU from 1985 to 2002 for craniotomy under general anaesthesia. Perioperative mortality (overall ) of that period was 5.5%. Perioperative mortality significantly reduced from 1985 to 2002. In first 6 years (1985 - 1990) mortality was 14%; in 2nd 6 years ( 1991 -1996 ) mortality was 6%; in 3rd 6 years (1997 -2002) mortality was only 2.48%. At the same time number of patients undergoing surgery greatly increased: In first 6 years ( 1985- 1990 ) it was 225 ; in 2nd 6 years ( 1991 - 1996 ) : 557 , in 3rd 6 years ( 1997 - 2002 ): 1169. All the above data shows markedly reduced mortality and increased number of surgery indicates tremendous improvement in the field of neuroanaesthesia both in drugs and monitors as well as skillness of neurosurgeons. To assess changes in outcome , outcome measures need to be defined for neuroanaesthesia. Because the effects of surgery markedly affect neurological or neurophysiological outcome, it can be difficult to distinguish the effects of surgery & anaesthesia and the effects of new agents. Journal of BSA, Vol. 18, No. 1 & 2, 2005 p.17-21